TRANSFORMATIVE LEADERSHIP AS A SOLUTION TO ACCELERATE SOCIAL DEVELOPMENT IN PAPUA - Muliadi Anangkota; Mohammad A. Musa’ad; Untung Muhdiarta (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Social development in Papua still faces complex challenges in the form of socio-economic inequality, low community participation, and weak trust in the government. This study aims to analyze the urgency of transformative leadership as a conceptual and strategic solution to accelerate equitable social development in Papua. This study uses a qualitative approach with discourse analysis methods on various secondary data sources, such as policy documents, previous research results, and relevant scientific literature. The analysis was conducted descriptively through the stages of data reduction, presentation, and drawing interpretive conclusions. The results show that social development in Papua is still top-down and has not optimally supported the local community. Transformative leadership has proven relevant because it is able to shift the development paradigm from an administrative one to a participatory one oriented toward humanitarian values. Transformative leaders act as agents of change who foster community awareness, trust, and independence by building on local cultural values such as mutual cooperation and deliberation. This study confirms that the synergy between inclusive policies, transformative leadership, and community participation is key to realizing equitable, inclusive, and sustainable social development in Papua